P.065 Physician Approaches to Anti-thrombotic Therapies for Acutely Symptomatic Carotid Stenosis: Insights from the Hot Carotid Qualitative Study. (November 2021) - Beland, B; Ganesh, A; Jewett, G; Campbell, DJ; Varma, M; Singh, R; Al-Sultan, A; Wong, J; Menon, BK
Abstract : Background: Whereas the beneficial effect of antiplatelet therapy for recurrent stroke prevention is well-established, uncertainties remain regarding the optimal anti-thrombotic regimen for acutely symptomatic carotid stenosis ("hot carotid"), particularly as patients await revascularization. We sought to explore the approaches of stroke physicians to peri-procedural anti-thrombotic management of patients with "hot carotids". Methods: We conducted semi-structured interviews regarding "hot carotid" management with purposive sampling of 20 stroke physicians from 14 centres in North America, Europe, Asia, and Australia. We identified key themes using conventional qualitative content analysis. Results: Important themes revealed from our discussion included limitations of existing clinical trial evidence, competing surgeon versus neurologist/internist preferences, and single vs dual antiplatelet therapy (DAPT) while awaiting revascularization. Areas of uncertainty included the management of stroke while on aspirin, implications of non-stenotic features of carotid disease (intraluminal thrombus, plaque morphology), the role of newer anti-platelet agents or anticoagulants, platelet aggregation testing, and how soon to start DAPT. Conclusions: Our qualitative analysis revealed themes that were important to stakeholders in stroke care. Teams designing international trials will have to accommodate identified variations in anti-thrombotic practice patterns and take into consideration areas of uncertainty, such as newer anti-thrombotic agents, and the implication of non-stenotic features of carotid disease.